Solar and heat pump systems for houses. (Solar Heating and Cooling., 2014)
The combination of heat pumps and solar components is a recent development and has great potential for improving the energy efficiency of house and hot water heating systems. As a consequence, it can enhance the energy footprint of a building substantially. This work compares different systems, analyses their performance and illustrates monitoring techniques. It helps the reader to design, simulate and assess solar and heat pump systems. Good examples of built systems are discussed in detail and advice is given on how to design the most efficient system.